MODERN HINDI POETRY AND WOMEN: आधुनिक हिंदी कविता और स्त्री.विमर्श - Devi, Pramila (International Journal of Research -GRANTHAALAYAH, 2017)
In the field of Hindi literature, along with men, women writers have also contributed significantly with their valuable works. Here the pages of the history of the past India are filled with specific works of Indian women. At that time they had an opportunity to get education like men. In the course of time, bad practices in the society started increasing. Along with the independence of the country, the freedom of women was also abducted. It also stripped them of the right to equality and education. हिंदी साहित्य के क्षेत्र में पुरूषों के साथ-साथ नारी साहित्यकारों ने भी अपनी बहुमूल्य कृतियों से उल्लेखनीय योगदान दिया है । यहाँ अतीत भारत के इतिहास के पृष्ठ भारतीय महिलाओं की विशिष्ट कृतियों से भरे पड़े हैं । उस समय उन्हें पुरूषों के समान शिक्षा प्राप्त करने का अवसर मिलता था । कालांतर में समाज में कुप्रथाएँ बढ़ने लगी । देश की आज़ादी के साथ-साथ स्त्रियों की आज़ादी का भी अपहरण हुआ । इसमें उनसे समानता और शिक्षा का अधिकार भी छीन लिया गया ।